2021
DOI: 10.1101/2021.07.09.451812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of temperature on the affinity of SARS-CoV-2 Spike for ACE2

Abstract: The seasonal nature in the outbreaks of respiratory viral infections with increased transmission during low temperatures has been well established. The current COVID-19 pandemic makes no exception, and temperature has been suggested to play a role on the viability and transmissibility of SARS-CoV-2. The receptor binding domain (RBD) of the Spike glycoprotein binds to the angiotensin-converting enzyme 2 (ACE2) to initiate viral fusion. Studying the effect of temperature on the receptor-Spike interaction, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…We also assessed the role of thermodynamics in the binding of RBD wt, RBD Q498Y and RBD to ACE2. In agreement with previous results by other groups (Pre ´vost et al, 2021), we observed that RBD-ACE2 binding is reduced at higher temperatures. This tendency is less accentuated in the RBD Q498Y mutant, yet decreased binding is still observed at 37 C. From a molecular point of view, these results suggest that at high temperatures the binding interfaces of RBD and ACE proteins have a reduced binding capacity, which could be a consequence of temperature-dependent protein plasticity and loss of an optimal conformation.…”
Section: Discussionsupporting
confidence: 93%
“…We also assessed the role of thermodynamics in the binding of RBD wt, RBD Q498Y and RBD to ACE2. In agreement with previous results by other groups (Pre ´vost et al, 2021), we observed that RBD-ACE2 binding is reduced at higher temperatures. This tendency is less accentuated in the RBD Q498Y mutant, yet decreased binding is still observed at 37 C. From a molecular point of view, these results suggest that at high temperatures the binding interfaces of RBD and ACE proteins have a reduced binding capacity, which could be a consequence of temperature-dependent protein plasticity and loss of an optimal conformation.…”
Section: Discussionsupporting
confidence: 93%
“…Flow cytometry analysis of cell-surface spike staining 10 mg of the different expressors of the original SARS-CoV-2 Spike (Hoffmann et al, 2020) or the different mutants of the SARS-CoV-2 Spike (B.1.1.7, D614G, D69-70, D144, N501Y, A570D, P681H, T716I, S982A and D1118H) (Li et al, 2021b;Prevost et al, 2021;Tauzin et al, 2021) were co-transfected with 2.5 mg of a green fluorescent protein (GFP) expressor (pIRES2-eGFP) into 2 3 10 6 293T cells using the standard calcium phosphate method. Before staining with primary antibodies, cells were washed 2 times.…”
Section: Sars-cov-2 Spike Elisa (Enzyme-linked Immunosorbent Assay)mentioning
confidence: 99%
“…Antibody concentrations (0 mg/mL, 0.01 mg/mL, 0.0316 mg/mL, 0.1 mg/mL, 0.316 mg/mL, 1 mg/mL, 3.16 mg/mL and 10 mg/mL) were performed in a separate 96 well culture plate using DMEM supplemented with penicillin (100 U/mL), streptomycin (100 mg/mL), HEPES, 0.12% sodium bicarbonate, 2% FBS and 0.24% BSA. 10 4 TCID 50 /mL of authentic SARS-CoV-2 D614G virus (derived from strain LSPQ/231457/2020 (Prevost et al, 2021)) was prepared in DMEM + 2% FBS and combined with an equivalent volume of diluted antibodies for one hour. After this incubation, all media was removed from the 96 well plate seeded with Vero E6 cells and virus:antibody mixture was added to each respective well at a volume corresponding to 600 TCID 50 per well and incubated for one hour further at 37 C. Both virus only and media only (MEM + 2% FBS) conditions were included in this assay.…”
Section: Microneutralization Assaymentioning
confidence: 99%
“…Pre-pandemic plasma samples were used as negative controls in cytometry assays (data not shown). The conformationally independent S2-specific monoclonal antibody CV3-25 was used as a positive control and to normalize Spike expression in flow cytometry assays, as described [4,[20][21][22][23]. Alexa Fluor-647-conjugated goat anti-human antibodies (Abs) able to detect all Ig isotypes (anti-human IgM+IgG+IgA; Jackson ImmunoResearch Laboratories, Cat # 109-605-064) were used as secondary Abs to detect plasma binding in flow cytometry experiments.…”
Section: Plasma Samples and Antibodiesmentioning
confidence: 99%
“…Samples were acquired on a LSRFortessa cytometer (BD Biosciences), and data analysis was performed using FlowJo v10.7.1 (Tree Star). The conformationally-independent anti-S2 antibody CV3-25, effective against all Spike variants, was used to normalize Spike expression, as reported [4,20,22,23].…”
Section: Cell Surface Staining and Flow Cytometry Analysismentioning
confidence: 99%